Endometriosis, Mental Health and Quality of Life - Paraskevi Theofilou (Journal of Public Health International, 2024)
This article explores links between endometriosis, mental health, and quality of life. It reviews symptom burden, comorbidity patterns, and multidisciplinary care approaches.
Keywords: chronic pelvic pain